[tex]a) b-\frac{10b-5}{5} =b-2b+1=-b+1\\\\b)\frac{8x-4}{4} -\frac{x}{2}=2x-1-\frac{1}{2}x=\frac{3}{2} x-1 ]]\\\\c)n-\frac{4n-1}{2} =n-2n+\frac{1}{2} =-n+\frac{1}{2} \\\\d)\frac{x-6}{3} -x=\frac{1}{3} x-2-x=-\frac{2}{3} x-2\\\\e)2(n-3)-\frac{6n+4}{2} =2n-6-3n-2=-n-8\\\\f)\frac{3a-10}{5} -2(6-5a)=\frac{3}{5} a-2-12+10a=-14+10\frac{3}{5} a\\\\g)\frac{2p+5}{6} +\frac{3-4p}{3} =\frac{2p+5}{6} +\frac{6-8p}{6} =\frac{2p+5+6-8p}{6} =\frac{-6p+11}{6} =-p+1\frac{5}{6} \\\\[/tex]
[tex]h)\frac{x+3}{2} -\frac{4x+2}{4} =\frac{2x+6}{4} -\frac{4x+2}{4} =\frac{2x+6-4x-2}{4} =\frac{-2x+4}{4}=-\frac{1}{2} x+1\\\\i)2m+\frac{3m-1}{5} -\frac{2m-3}{15} =\frac{30m}{15} +\frac{9m-3}{15} -\frac{2m-3}{15}=\frac{30m+9m-3-2m+3}{15}=\frac{37m}{15} =2\frac{2}{15} m[/tex]
Pozdrawiam.